Analisis Minat Belajar Siswa Kelas VI SD N 03 Klaling terhadap Pembelajaran Matematika - Silvia Maulinnikmah; Moh Zulfan Sauqi; Muhammad Zaki Ali; Fina Fakhriyah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Interest in learning is one of the important factors that play a role in the success of mathematics learning in elementary schools. However, there are still many students who show low interest in learning mathematics because it is considered difficult and confusing. This study aims to analyze the level of interest in learning mathematics of grade VI students of SD N 03 Klaling. The study used a quantitative approach with a survey method. The subjects of the study were all 27 grade VI students. The instrument used was a questionnaire containing 10 statements with a four-level Likert scale to measure three aspects of interest in learning: interest, participation, and motivation. The results showed that the average percentage of students' interest in learning reached 73.4%, which is included in the high category. As many as 40.7% of students were in the strongly agree category and 59.3% of students were in the agree category, with no students included in the low interest category. These findings indicate that students generally have a good interest in learning mathematics. Therefore, innovative learning strategies are needed that are in accordance with student characteristics to maintain and improve students' interest in learning.